Cyanobacteria inoculation as a potential tool for stabilization of burned soils. (1st January 2020) - Chamizo, Sonia; Adessi, Alessandra; Certini, Giacomo; De Philippis, Roberto
Abstract : The practice of "cyanobacterization" (soil inoculation with cyanobacteria) has been shown to be effective in increasing soil fertility and physical stability in natural and agricultural soils, but little is known about its utility for the recovery of burned soils. To partly fill this knowledge gap, we inoculated two cyanobacterial species, Phormidium ambiguum and Scytonema javanicum, in two burned sterilized soils having contrasting properties, and incubated them under laboratory conditions for 45 days. The development of a cyanobacterial biocrust induced by the inoculum was evident and confirmed by the significant increase in chlorophyll a content compared to control soils. Hydrophobicity, surface penetration resistance, and exopolysaccharide content of the two soils were also evaluated. Cyanobacteria inoculation significantly decreased soil hydrophobicity, as assessed by the lower repellency index 15 days after the inoculation compared to the control soils. A significant increase in penetration resistance was recorded in the inoculated samples compared to control ones after 45 days of soil incubation. The effect of cyanobacteria inoculation depended on the characteristics of the burned soil, being more marked in the soil finer in texture, richer in organic carbon and nitrogen, and with lower initial soil hydrophobicity. In conclusion, this study points to the potential of cyanobacterization for the stabilization and recovery of soils in burned areas, which is one of the major concerns in postfire management to avoid net soil loss and major hydrogeological issues.